Achieving a nutrition revolution for Africa: The road to healthier diets and optimal nutrition - Covic, Namukolo; Hendriks, Sheryl L. (International Food Policy Research Institute, 2016)
Focusing the 2015 Annual Trends and Outlook Report (ATOR) on nutrition will contribute to a broader understanding of the critical role of nutrition in achieving international, continental, and national economic growth targets through agriculture, food security, and nutrition. This report presents information and analysis in support of evidence-based policy making that should inform the second generation of CAADP national investment plans now being developed. This is an important moment for shaping the region’s future and ensuring that the much-needed agriculture-led growth and development agenda can simultaneously deliver on improving nutrition, saving lives, improving productivity and health, and curbing nutrition-related diseases and the associated public health expenditures. These investment plans should address not only the usual elements of undernutrition but also widespread micronutrient deficiencies (termed “hidden hunger”) and the growing problem of overweight and obesity that is associated with economic growth.